2018
DOI: 10.1016/j.neuroscience.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Behavior and EEG Oscillations in Aged Dp(16)1Yey/+ Mice: A Down Syndrome Model

Abstract: Down syndrome (DS) results from the triplication of genes located on human chromosome 21 (Hsa21). Though many cognitive and behavioral impairments are associated with DS, sleep disturbances remain poorly understood despite being a reported phenotype in approximately 60% of individuals diagnosed with DS. In this study, sleep and electroencephalography (EEG) oscillations were recorded from aged (12-14 mos.) Dp(16)1Yey/+ mice (Dp16), a mouse model of DS. We observed disrupted sleep demonstrated by increased activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
2
10
3
Order By: Relevance
“…Previous studies that have interrogated hippocampal function in similar mutant mouse populations (Aziz et al, 2018;Levenga et al, 2018) have found no impairments of mnemonic function in Dp10Yey mice (Belichenko et al, 2015;Yu et al, 2010b). In contrast, we observed decreased alternation rates in Dp10Yey mice suggestive of a spatial working memory deficit (Deacon and Rawlins, 2006).…”
Section: Discussioncontrasting
confidence: 61%
“…Previous studies that have interrogated hippocampal function in similar mutant mouse populations (Aziz et al, 2018;Levenga et al, 2018) have found no impairments of mnemonic function in Dp10Yey mice (Belichenko et al, 2015;Yu et al, 2010b). In contrast, we observed decreased alternation rates in Dp10Yey mice suggestive of a spatial working memory deficit (Deacon and Rawlins, 2006).…”
Section: Discussioncontrasting
confidence: 61%
“…This finding is consistent with previous reports of impairment of Dp16 mice in other tasks that require hippocampal function, e.g., Morris Water Maze and Contextual Fear Conditioning, and of hippocampal learning deficits in other mouse models of DS, including Ts65Dn and Ts1Cje mice, each of which is trisomic for a subset of the genes that are trisomic in the Dp16 mice (56,61,(64)(65)(66)(67). This finding is also consistent with previous studies that showed that Dp16 mice display abnormal hippocampus-based long-term potentiation (LTP) (60,61,67,68).…”
Section: Discussionsupporting
confidence: 90%
“…The sleep phenotype of Ts65Dn and Ts1Cje mice carrying one extra copy of partially overlapping segments of mouse chromosome 16, was reported in our previous study in which Ts65Dn mice showed increased waking amounts at the expense of non-REM sleep though Ts1Cje mice had no sleep or EEG abnormalities 40 . Recently, it was reported that aged Dp16 mice spend more time awake with the frequent transition from sleep to wakefulness www.nature.com/scientificreports/ and decreased delta power during non-REM sleep, similarly in sleep phenotype to Ts65Dn mice 41 . Although the occurrence of OSA has not been explored in these models so far, these findings are consistent with sleep disturbances found in individuals with DS.…”
Section: Discussionmentioning
confidence: 99%